Epidemiology and survival of cervical cancer in Iran based on national cancer registry data (2008-2014) - Akbari, Atieh; Khayamzadeh, Maryam; Salmanian, Reza; Moradi, Afshin; Akbari, Mohammad Esmaeil (Frontiers in Oncology, 2023)
Background: Cervical cancer (CC) is the third most commonly diagnosed cancer and the fourth leading cause of cancer death in females worldwide, associated with the incidence of human papillomavirus (HPV) infection. The CC incidence is low in Iran, ranking 11th among cancers. This study aimed to estimate the survival rate of CC and the reasons for its low survival rate based on the data retrieved from the Iranian National Cancer Registry System. Methods: In this retrospective cohort study, data for patients diagnosed with CC from 2008 to 2014 were collected and analyzed. The Kaplan-Meier method was used for survival analysis based on epidemiological and clinical factors. Results: A total of 5,304 women were diagnosed from March 10, 2008 to March 9, 2014 and 2,423 patients were followed. The mean age of the cases was 51.91 years, and 65.91% were alive. The 5- and 10-year survival rates were 58% and 50%, respectively, with no difference between younger cases with SCC or AC but better survival rates for older patients with SCC. Conclusions: As a preventable disease, CC is related to biological factors and geographical and sociodemographic indices. Geographical, cultural, and religious behaviors affect the CC incidence and survival. In Iran, the 5-year survival rate ranges from 34% to 70% among different geographic regions. Hence, effective screening based on cultural and sociodemographic issues is recommended.